Globalizing Shanghai: International migration and the global city - Wei Shen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Cities are the focal point for the mobility of talents, located between the nations and firms, states and educational institutions. Shanghai, being regarded as the 'ultimate poster-child for the effects of globalization on cities and regions' by the BBC (2007), the city is argued as the best candidate for China's global city (Ni 2008, Lin 2004, Wu and Yusuf 2004). However, one major obstacle in Shanghai's pathway in becoming a global city is the shortage of skilled labour. Shanghai now is inevitably competing with other cities in China and Asia for the best brains in the world. This paper therefore aims to understand the relationship and linkage between global cities and the migration of talents. By using the case study of the circulating network and mobility of Chinese student migration from elite business schools in France to illustrate its role in Shanghai's competitiveness and trajectory to become China's global city.
Keywords: J61; R10; R63; F20; 330; international migration; global cities; talents; brain drain; China; Shanghai